Validation of a Risk Assessment Instrument for Juvenile Probationers in Alameda County, California, 1996 ([Verlag nicht ermittelbar], 2001)
This study sought to develop a risk assessment instrument to be used in the placement of adjudicated juveniles and determination of outcomes for juvenile probationers. The following research questions served as a guide in developing the risk assessment instrument: (1) Does the instrument measure what it purports to measure? (2) Do similar cases receive similar recommendations for placement services? (3) Is the instrument fair to dissimilar groups? (4) Is the instrument useful to practitioners? and (5) Will the instrument be simple to implement? The goal of the new risk assessment instrument was to address the relative risk of recidivism without taking into account the severity of the current offense. In order to develop a new risk assessment instrument, researchers adapted a pre-existing instrument that had been used and validated with juvenile probationers in California. The new instrument was used to evaluate youths for three measures of recidivism: intake actions, petitions filed, and petitions sustained through one year after the placement decisions were made. The sample of youths was comprised of those who in 1996 had received either a field supervision or a placement order as a disposition. The instrument measured age at first finding, prior criminal behavior, institutional commitments or placement of 30 consecutive days or more, drug/chemical use, alcohol use, parental skills, school disciplinary problems, and peer relationships.